A Cosmopolitan History of Archaeology: The Olov Janse Case. (19th February 2014) - Källén, Anna; Hegardt, Johan
The life of international archaeologist Olov Janse (1892–1985) demonstrates the complexity of personal identify formation. Janse worked in Europe, Scandinavia, South East Asia and North America, spoke many different languages, controlled many collections of artefacts, changed identity or character at least five times, and nationality, three times. It is hoped the themes, elucidated through Janse's story, will encourage comparisons with, and analyses of, the careers of other cosmopolitan archaeologists, and instigate an international history of archaeology focused on mobility, translation and networks, rather than one based on the impact of archaeology on the development of nation-states.